Aplikasi Pengukuran Tahanan Tanah Terhadap Penekanan Plat Dalam Penentuan Parameter Desain Roda Besi Bersirip - Wawan Hermawan (Jurnal Keteknikan Pertanian, 2009)
Plat penetration resistance on paddy soil was measured for determination of a lug wheel designparameters. A penetrometer equipped with plat tips (three plat sizes) was used for soil penetrationmeasurement at 30o, 45o, 60o, 75o and 90o penetratiron angle, at the depth of 2.5 cm, 5 cm, 7.5 cm, 10 cm,12.5 cm, 15 cm, 17.5 cm dan 20 cm. The results showed that using plat inclination angle of 45o, producedhighest horizontal and vertical soil reaction forces. In the paddy soil with a deeper mud layer condition,soil reaction forces tended to significantly increase at 0-10 cm depth and at 15-20 cm depth. The soilreaction force at 15-20 cm depth at 90o penetration angle was 60 kPa. For the location, the optimum lugwheel design parameters were: 14 lugs, 8 cm lug height, 35 cm lug width, and 85 cm wheel diameter. Fora shallower mud layer paddy soil, the soil resistance significantly increased at 6-20 cm depth. Penetrationresistance at 15-20 cm depth at 90o penetration angle was higher than 90 kPa. The optimum lug wheeldesign parameters were: 14 lugs, 10 cm lug height, 35 cm lug width, and 85 cm wheel diameter.Keywords : paddy soil, plat penetration, soil resistance, lug wheel, designDiterima: 25 Pebruari 2009; Disetujui: 12 Juni 2009